The Impact of the Covid-19 Pandemic on the Universal Basic Income Debate - Chung, Seongwon (Technium Social Sciences Journal, 2020)
The development of AI industries, rapidly changing technologies, and the severe inequality of wealth in the current society have increased the relevance of “Universal Basic Income” (UBI), a welfare policy where the government distributes monetary sums to every member of society regardless of socioeconomic status. In Korean Society, this has been a political issue for years and debates have been going on. Basic income has emerged as a central topic in Korean politics in preparation for the "post-corona" era. With big-name politicians from the ruling and opposition parties expressing their views, it is the first time that a "welfare issue" has occupied the heart of the political discourse since the 2010 free school lunch debate. In this paper, the disparity of expectations of UBI and the reality showed during the pandemic will be assessed using five criteria: technical capability, economic capability, social and ethical capability, political capability, and administrative capability.